Butylphthalide Combined With Conventional Treatment Attenuates MMP-9 Levels and Increases VEGF Levels in Patients With Stroke: A Prospective Cohort Study - Xiong, Yingqiong; Liu, Juanjuan; Xu, Yang; Xie, Shu; Zhou, Xinhua; Cheng, Shaomin (Frontiers in Neurology, 2021)
Background and purpose Butylphtalide increases the vascular endothelial growth factor (VEGF) and decreases matrix metalloproteinase (MMP)-9 in animal models of stroke and might be of use in the management of stroke. To explore whether butylphthalide combined with conventional treatment can change the levels of MMP-9 and VEGF and the National Institutes of Health Stroke Scale (NIHSS) scores of patients with stroke. Methods This was a prospective cohort study involving inpatients admitted to the Jiangxi Provincial People's Hospital (January-June 2019) due to acute cerebral infarction. The patients received conventional treatments with or without butylphthalide. The changes in the NIHSS scores were compared between groups. Plasma MMP-9 and VEGF were measured by enzyme-linked immunosorbent assay. Results Twenty-four patients were included in the conventional treatment group and 46 in the butylphthalide group. The butylphthalide group showed lower MMP-9 (130 ± 59 vs. 188 ± 65, p = 0.001) and higher VEGF (441 ± 121 vs. 378 ± 70, p = 0.034) levels on day 6 compared with the conventional treatment group. The changes in MMP-9 and VEGF were significant, starting on day 3 in the butylphthalide group but on day 6 in the conventional treatment group. There were no differences between the two groups in the NIHSS scores at admission and at discharge (all p > 0.05). The overall response rate was higher in the butylphthalide group compared with the conventional treatment group (63.0% vs. 37.5%, p = 0.042). Conclusions Butylphthalide combined with conventional treatment can decrease MMP-9 levels and increase VEGF levels. The patients showed reduced NIHSS scores, possibly suggesting some improvement in prognosis after stroke. Still, the conclusions need to be confirmed in a larger sample and in different etiological subtypes of stroke.